Out of work, out of leisure, out of place: Moral regulation, citizenship and volunteering in the rural "Idyll" - Law, Alan; Harrington, Maureen; Wearing, Michael (The Greek Review of Social Research, 2011)
This paper presents components of semi-structured interview exploratory research (n=25) carried out during 2003in NSW's far north coast rainbow region as preparation of a larger agenda which seeks to interrogate ways in which national policy that circumscribes citizenship, interacts with cultural practices of belonging in rural "idyllic" tourism regions subjected to rapid growth in immigration from urban environments in successive waves. The central thrust of our approach is to examine the way in which work-for-the-dole volunteering, with it's emphasis on producing the active citizen in the bodies of the unemployed, operates to inform cultural practices of place infused with diverse, contradictory, and intersecting meanings of idleness bound up in culturally mediated relationships between joblessness and leisure. Though barely scratching the surface of highly complex and fluid relations, the paper focuses on how obligatory volunteering operates to both subvert and support the extent to which work-for the-dole ameliorates social alienation as a condition of joblessness. What happens to the sense of belonging when layers of regional migrants are pushed together by the welfare system